Design and Implementation of Algorithms for Compensating the Effect of Linear Acceleration on Angular Velocity Measurements by MEMS Gyroscopes - Spáčil, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Tato Disertační práce se zabývá vývojem nového typu dopředného kompenzátoru, speciálně určeného k potlačení vlivu lineárního zrychlení a ryvu působícího na MEMS gyroskopické senzory. Z principu funkce inerciálního snímače, dochází při umístění gyroskopického senzoru mimo osu rotace k vzniku dalších nežádoucích sil (normálové a tečné), které negativně ovlivňují měření žádané úhlové rychlosti. Přítomnost těchto sil je však možno měřit nezávislým senzorem, akcelerometrem, a vhodným způsobem kompenzovat výstupní hodnotu gyroskopického senzoru a tím zpřesnit nepřímo měřenou hodnotu úhlové rychlosti. V první části práce identifikujeme vliv zmíněných zrychlení na MEMS gyroskopy, v drůhé části práce pak navrhneme a otestujeme různé kompenzátory, vyhodnotíme jejich efektivitu a v třetí části vhodný algoritmus implementujeme na RT HW.

This Dissertation deals with the development of a new type of forward compensator, specifically designed to counteract the effect of linear acceleration and jerk acting on MEMS gyro sensors. From the principle of inertial sensor function, additional undesirable forces (normal and tangential) occur when the gyro sensor is placed off the axis of rotation, which negatively affect the measurement of the desired angular velocity. However, the presence of these forces can be measured by an independent sensor, the accelerometer, and the output value of the gyro sensor can be compensated for in a suitable way, thus refining the indirectly measured value of the angular velocity. In the first part of the paper we identify the effect of the mentioned accelerations on MEMS gyroscopes, in the second part of the paper we design and test different compensators, evaluate their effectiveness and in the third part we implement a suitable algorithm on RT HW.
Design and Implementation of Algorithms for Compensating the Effect of Linear Acceleration on Angular Velocity Measurements by MEMS Gyroscopes
Keywords: MEMS senzory; gyroskop; akcelerometr; dopředný kompenzátor; mechatronika; Matlab; Simulink; FPGA; mikrokontrolér; výpočty v reálném čase.; MEMS sensors; gyroscope; accelerometer; feedforward compensator; mechatronics; Matlab; Simulink; FPGA; microcontroller; real-time calculations.